A New Biometric Based Secret Key Exchange Scheme for Wireless Body Area Networks (Damascus University Journal for engineering sciences, 2021)
A Wireless Body Area Network (WBAN) is a wireless network of health monitoring sensors, designed to deliver healthcare. The confidentiality and integrity of the health information in WBAN is particularly important because of the negative effect of security attacks on the patient’s life. Secret key exchange is one of the most important issues in WBAN security. In this paper, we propose a new secret key exchange scheme for the aim of generating and distributing secret keys between WBAN sensors. Our scheme depends on biomedical features for generating and distributing the secret keys. We specifically use the electrocardiogram signal features in the time domain and the frequency domain. Our proposed scheme has several advantages such as: simplicity of processing operations, ability of generating time variant secret key, operating through plug-n-play manner (no previous key distribution is needed), ensuring the security of WBAN in the startup time, ability to authenticate the communicated sensors, tolerance with poor synchronization between sensors, and tolerance with slight dissimilarity of signal measured by different sensors in the same network. We built our scheme, tested it, and demonstrated its advantages over the proposed scheme in previous studies.
Keywords: Wireless Body Area Network (WBAN); Secret keys exchange scheme; Biometric key; Electrocardiogram (ECG); Authentication